Mixed Bohr radius in several variables - Galicer, Daniel Eric (2019)
Let K(Bℓnp , Bℓnq ) be the n-dimensional (p, q)-Bohr radius for holomorphic functions on Cn. That is, K(Bℓnp , Bℓnq ) denotes the greatest number r ≥ 0 such that for every entire function f(z) = Σ α aαzα in n-complex variables, we have the following (mixed) Bohr-type inequality: sup Σ |aαzα| ≤ sup |f(z)|, z∈r·Bℓn z∈Bℓn α q p where Bℓn denotes the closed unit ball of the n-dimensional sequence space ℓn r . r For every 1 ≤ p, q ≤ ∞, we exhibit the exact asymptotic growth of the (p, q)-Bohr radius as n (the number of variables) goes to infinity.